Mechanical energy converter from linear displacement - Yip, James Jun Wei. (2010)
Harnessing waste energy has been an increasing trend in today’s context. This is due to the pollution in all forms due to the production of electricity. Hence, the need to find ways to reuse waste energy is heavily researched on. In this project, the waste energy that was going to be reused was that of the deceleration of a vehicle as it moves over a hump. A prototype was made to justify the feasibility of such a concept. This project was a continuation from the previous student’s work and was under the supervision of A/P Yeo Joon Hock.